THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE, AND PRICE ON PURCHASE DECISIONS OF TOMORO COFFEE AMONG THE COMMUNITY IN MEDAN MAIMUN DISTRICT - Stevani; Jesslyn Tanie; Nurmaidah Ginting; Emma Novirsari (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to determine the influence of product quality, brand image and price on the purchase decision of Tomoro Coffee. The research method used in this study is a quantitative research method. The population in this study consists of the residents of Medan Maimun District who have tasted coffee at Tomoro Coffee, with an unknown exact population size. The sampling technique used is non-probability sampling. The sample size was determined using Slovin’s formula, resulting in a total of 100 respondents. The data analysis method applied in this study is multiple linear regression analysis. The results of the study show that, partially, product quality affects the purchase decision of Tomoro Coffee, brand image affects the purchase decision of Tomoro Coffee and price affects the purchase decision of Tomoro Coffee. Simultaneously, product quality, brand image, and price influence the purchase decision of Tomoro Coffee. The purchase decision of Tomoro Coffee is influenced by product quality, brand image, and price by 41.5%, while the remaining 58.5% is influenced by other variables not examined in this study